Mobility management in third-generation all-IP networks. - Chiussi, F.M (IEEE Communications magazine)
It is now widely recognized that using IP as the foundation for next-generation mobile networks makes strong economic and technical sense, since it takes advantage of the ubiquitous installed IP infrastructure, capitalizes on the IETF standardization process, and benefits from both existing and emerging IP-related technologies and services. The large-scale support of data services and their integration with legacy services are the common objectives of all wireless efforts termed third generation (3G) and beyond. In these all-IP wireless networks, IP can be deployed in two modes: the transport mode and the native mode. As we show in this article, this duality in the use of IP has a significant impact on network efficiency and performance. It is the extended native use of IP in the terrestrial segment of a wireless operator's domain that more readily allows for building a converged network with multiple access technologies. We then discuss the different levels of mobility in the all-IP network. In particular, our focus is on micromobility, and on the issue of seamless localized mobility within the converged network. After reviewing the mobility schemes that have emerged in previous years, we describe a hierarchical mobility management scheme based on multiprotocol label switching (MPLS). The scheme employs an enhanced type of MPLS routers, called label edge mobility agents, and is scalable, efficient, and flexible. It directly inherits the noted capabilities of MPLS in terms of support of QoS, traffic engineering, advanced IP services, and fast restoration. This scheme does not use nodes that are specific to any given wireless technology, and is well suited for gradual deployment